2021
DOI: 10.1111/iwj.13567
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative healing in the diabetic foot is impacted by discharge destination

Abstract: The aim of this study was to evaluate the impact of discharge destination on diabetes‐related limb salvage surgery outcomes post‐hospitalisation. This was a single‐centre, observational, descriptive study of 175 subjects with diabetes who underwent limb salvage surgery of a minor foot amputation or wide incision and debridement for an acutely infected diabetic foot ulcer (DFU). Comparisons were made between subjects discharged home vs a skilled nursing facility (SNF) for 12 months postoperatively. Univariate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
3
4
0
Order By: Relevance
“…The median length of stay in hospital in our study was 10 days. This is similar to other studies (Burmeister et al, 2021;Rosi et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The median length of stay in hospital in our study was 10 days. This is similar to other studies (Burmeister et al, 2021;Rosi et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…The median length of stay in hospital in our study was 10 days. This is similar to other studies (Burmeister et al., 2021; Rosi et al., 2021). However, it has been shown that length of stay is longer among patients who have had a major amputation compared to those who have been treated with minor amputation or conservatively without surgical intervention (Rosi et al., 2021; Syed et al., 2022).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This supports recent literature, which suggests that patients who are discharged to SNF after an operation have increased morbidity and mortality and are more likely to develop infection. [5][6][7] Discharging a patient to an SNF is also more costly than discharge to home health care 4,17 and expenditures increase further when the patients that are discharged to SNF experience complications. In an ideal situation, all patients would be able to go home safely after surgery and would not require the extra care provided by subacute rehabilitation facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are discharged to home or a subacute setting, such as a skilled nursing facility (SNF) or acute rehabilitation after surgery. Discharge to SNF may have unintended consequences such as increased cost and increased risk of infection 4–7 . The inpatient physical therapy evaluation (PTE) is critical for discharge planning, but the role of this assessment in discharge planning has not been fully elucidated after cervical spine surgery for DCM 8 …”
mentioning
confidence: 99%